Acromioclavicular joint dislocation treated with Bosworth screw and additional K-wiring: results after 7.8 years – still an adequate procedure? - Tiefenboeck, Thomas M. (BMC Musculoskelet Disord, 2017)
BACKGROUND: The acromioclavicular (AC) joint dislocation is a major reason for shoulder instability. Different concepts of treatment and surgical methods are described in the literature. Thus, the purpose of this study was to present our data of long-term follow-up of patients having undergone treatment of acromioclavicular (AC) joint dislocation using the Bosworth Screw with additional K-wiring. METHODS: This study was conducted as a retrospective single centre data analysis. All patients treated operatively for AC joint dislocation with a Bosworth screw and additional K-wire fixation at our Department were asked to participate in this study. RESULTS: The study population consisted of 22 patients, 20 male and 2 female, with a mean age of 40 years ±15.6 years. Three grade-II lesions, 13 grade-III lesions, four grade-IV lesions and two grade-V lesions according to the Rockwood classification were found. The overall mean clinical outcome at the latest follow up was: Constant 95, DASH 6.4, ASES 94.6, SST 99.02, UCLA 33.1, ACJI 91.82 and VAS 0.29 – representing a good-to-excellent long-term outcome in all patients after at least 2 years follow-up (range; 2 - 19 years). Overall, 19 patients (86%) reported to be very satisfied with the achieved result, 15 patients (68%) reported to be able to participate in every sports activity and 16 patients (73%) reported to be able to perform their daily work without limitations. Overall, complications occurred in three patients (14%). Only one patient remained unsatisfied with the achieved result. CONCLUSION: Summarizing, our reported results showed that surgical fixation of acute AC joint dislocation with a Bosworth screw and additional K-wire fixation leads to good-to-excellent functional outcome and highly satisfactory results in the majority of patients. Despite its complications, in accordance with our results, Bosworth screw fixation with additional K-wiring in AC joint dislocation represents an adequate surgical procedure. Level of Evidence: Level IV, retrospective study.